Scratch-resistant glass and method of manufacture
A lithium aluminum silicate glass with a controlled ion exchange process enhances scratch resistance by creating a specific stress profile, addressing the inadequacies of existing ion-exchanged glasses in resisting scratches from rigid materials.
Patent Information
- Application Number
- JP2021557900
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-03-23
AI Technical Summary
Existing ion-exchanged glasses, despite improving surface strength, still suffer from inadequate scratch resistance when exposed to materials with higher rigidity.
A lithium aluminum silicate glass composition with controlled ion exchange, creating a stress profile that includes a spike layer depth of 4 μm or more, an average compression stress of 15 μm to 40 μm, and a specific molar ratio of potassium and sodium oxides, enhancing scratch resistance.
The stress profile significantly improves the scratch resistance of the glass, reducing the likelihood of transverse cracking under load, making it suitable for protective applications.
Smart Images

Figure 0007621269000011 
Figure 0007621269000012 
Figure 0007621269000013
Abstract
Description
Related Applications
[0001] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 826,300, filed March 29, 2019, the contents of which are relied upon and incorporated by reference in their entirety herein. [Technical field]
[0002] This disclosure relates generally to scratch resistant glass. More specifically, this disclosure relates to a method for providing glass with improved scratch resistance. [Background technology]
[0003] Ion-exchanged glasses are widely used as protective glasses and in the housings of electronic devices. Although ion exchange provides increased surface strength to the glass, including improved hardness, the glass remains susceptible to scratching when in contact with materials harder than glass.
[0004] Attempts to improve scratch or abrasion resistance typically involve manipulating the composition of the glass itself to increase hardness, using alternative materials, or applying a hard coat to the glass surface. For example, lithium-based glasses have been developed with improved mechanical performance. The Li-based glasses have been shown to have excellent drop performance, and these glasses can be dropped from even greater heights without breakage (fracture / breakage of the glass). To improve scratch performance along with other mechanical performance, boron can be added to open up the densely packed network of the glass.
[0005] Improving the scratch performance of portable devices has been a continuing challenge for glass manufacturers and portable device manufacturers. Summary of the Invention [Problem to be solved by the invention]
[0006] Thus, there is a need for glasses that can be strengthened, such as by ion exchange, and that have mechanical properties that enable them to be formed into scratch resistant glass articles. [Means for solving the problem]
[0007] Aspects of the present disclosure relate to glass-based articles and methods of making same.
[0008] In one embodiment, the glass-based article comprises a lithium aluminosilicate composition; varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) of 4 μm or greater and 8 μm or less; spike ); and a molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm, the molar ratio being greater than or equal to 0 and less than or equal to 1.8.
[0009] In one embodiment, the glass-based article comprises a lithium aluminosilicate composition; varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) of 4 μm or greater and 8 μm or less; spike ); and the average compressive stress (CS ) from 15 μm to 40 μm deep of 115 MPa or more avg ).
[0010] In one embodiment, the glass-based article comprises a glass-based article having a non-zero concentration of sodium extending from the surface of the glass-based article to the depth of the glass-based article; an average compressive stress (CS ) of 150 MPa or greater extending from 15 μm to 40 μm; avg ); and a molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm, the molar ratio being greater than or equal to 0 and less than or equal to 1.8.
[0011] In one aspect, a method of making a glass-based article includes the steps of subjecting a glass-based substrate having opposed first and second surfaces defining a substrate thickness (t), the substrate having a lithium aluminosilicate composition, to an ion exchange treatment comprising a molten salt bath having a sodium salt concentration ranging from 8 mol % to 100 mol %; and varying non-zero concentrations of sodium extending from a surface of the glass-based article to a depth of the glass-based article; a spike layer depth (DOL) ranging from 4 μm to 8 μm from the surface; spike ), and a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO) averaged over a distance from the surface to a depth of 0.4 μm is greater than or equal to 0 and is less than or equal to 1.8.
[0012] Additional features and advantages are set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.
[0013] It is to be understood that both the foregoing general description and the following detailed description are intended to describe various embodiments and provide an overview or framework for understanding the nature and features of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated in and constitute a part of this specification. The drawings illustrate various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]
[0014] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several embodiments described below. [Figure 1] FIG. 1 shows a schematic cross-section of glass having a compressive stress layer on a surface thereof according to embodiments disclosed and described herein. [Diagram 2] FIG. 1 is a schematic diagram of a stress profile including an inflection point stress. [Figure 3A]FIG. 1 is a plan view of an exemplary electronic device incorporating any of the glass articles disclosed herein. [Figure 3B] FIG. 3B is a perspective view of the example electronic device of FIG. 3A. [Figure 4] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for one embodiment. [Diagram 5] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for a comparative example. [Figure 6] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for a comparative example. [Figure 7] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for one embodiment. [Figure 8] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for one embodiment. [Figure 9] 1 is a graph of stress (MPa) versus position from the surface (μm) for embodiments and comparative examples of glass-based articles. [Figure 10] 1 is a graph of stress (MPa) versus position from surface (μm) for embodiments of glass-based articles. [Figure 11] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for one embodiment. [Figure 12] 1 is a graph of stress (MPa) versus position from surface (μm) for embodiments of glass-based articles. [Figure 13] 1 is a graph of oxide molarity as a function of depth in a glass article from a first surface (0 μm) for a comparative example. [Figure 14] 1 is a graph of stress (MPa) versus position from the surface (μm) for a comparative glass-based article. [Figure 15]1 is a graph of stress (MPa) versus position from the surface (μm) for embodiments and comparative examples of glass-based articles. [Figure 16] 1 is a graph of stress (MPa) versus position from the surface (μm) for embodiments and comparative examples of glass-based articles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Before describing several example embodiments, it is to be understood that the disclosure is not limited to the details of construction or process steps set forth in the following disclosure. The disclosure presented herein is susceptible to other embodiments and to being practiced or carried out in various ways.
[0016] Throughout this specification, reference to "one embodiment," "a particular embodiment," "various embodiments," "one or more embodiments," or "an embodiment" means that a particular feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of the disclosure. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "various embodiments," "in one embodiment," or "in an embodiment" in various places throughout this specification do not necessarily refer to the same embodiment or to only one embodiment. Furthermore, the particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.
[0017] Definitions and Measurements The terms "glass-based article" and "glass-based substrate" are used to include any object that is composed entirely or partially of glass. Laminated glass-based articles include laminates of glass and non-glass materials, and laminates of glass and crystalline materials. The glass-based substrate according to one or more embodiments can be selected from soda-lime silicate glasses, alkali-aluminosilicate glasses, alkali-containing borosilicate glasses, and alkali-containing aluminoborosilicate glasses.
[0018] "Base composition" is the chemical composition of the substrate prior to any ion exchange (IOX) processing. That is, the base composition is not doped with any ions from IOX. The composition at the center of an IOX-processed glass-based article is typically the same as the base composition when the IOX processing conditions are such that the ions provided for IOX do not diffuse to the center of the substrate. In one or more embodiments, the core composition at the center of the glass article comprises the base composition.
[0019] It should be noted that the terms "substantially" and "about" may be used herein to express the inherent degree of uncertainty that may result from any quantitative comparison, value, measurement, or other representation. These terms are also used herein to express the degree to which a quantitative representation may vary from a stated reference without causing a change in the basic functionality of the subject matter at issue. Thus, for example, a glass-based article that is "substantially free of MgO" is an article in which MgO has not been actively or batch-added to the glass-based article, but may be present in very small amounts as a contaminant. As used herein, the term "about" means that amounts, sizes, formulations, parameters, and other quantities and characteristics are not, and need not be, precise, are approximate, and / or may be greater or less, as desired, reflecting tolerances, conversion factors, rounding, measurement errors, etc., and other factors known to those of skill in the art. When the term "about" is used in describing a value or an endpoint of a range, it should be understood that the disclosure includes the specific value or endpoint referred to. Regardless of whether or not an endpoint of a numerical value or range is referred to herein as "about," it is intended that the endpoint of the numerical value or range include two embodiments: one modified by "about" and one not modified by "about." It is further understood that each endpoint of the range is significant both in relation to the other endpoint, and independently of the other endpoint.
[0020] Unless otherwise specified, all compositions described herein are expressed in mole percent (mol%) on an oxide basis.
[0021] A "stress profile" is the stress as a function of thickness throughout a glass-based article. The compressive stress region is the region extending from the first surface to the depth of compression (DOC) of the article where the article is under compressive stress. The central tension region extends from the DOC and includes the region where the article is under tensile stress.
[0022] As used herein, depth of compression (DOC) refers to the depth at which stress changes from compressive stress to tensile stress within a glass-based article. At DOC, stress goes from positive (compressive) stress to negative (tensile) stress, and thus indicates a stress value of 0. According to the conventions commonly used in the mechanical field, compression is expressed as a negative (<0) stress and tension is expressed as a positive (>0) stress. However, throughout this specification, a positive value of stress is a compressive stress (CS) expressed as a positive value or absolute value, i.e., CS=|CS|, as recited herein. Furthermore, a negative value of stress is a tensile stress. However, when used with the term "tensile", stress or central tension (CT) may be expressed as a positive value, i.e., CT=|CT|. Central tension (CT) refers to the tensile stress in the central region or central tension region of a glass-based article. Maximum central tension (max CT or CT max ) may occur at a central tension region of nominally 0.5 t, where t is the article thickness, but this allows for variation in the location of maximum tensile stress from the exact center. Peak tension (PT) refers to the maximum tension measured, which may or may not be the tension at the center of the article.
[0023] The "knee" of a stress profile is the depth in an article where the stress profile transitions from a steep to a gentle slope. The knee may also refer to a transitional region over a range of depths where the slope changes. Knee-point stress CS k The deeper part of the CS profile corresponds to the spike depth (DOL sp ) is defined as the value of compressive stress that can be extrapolated to the DOL measured by a surface stress meter using known methods. sp A schematic diagram of the stress profile including the inflection point stress is presented in Figure 2.
[0024] A non-zero metal oxide concentration that varies from the first surface to the depth of layer (DOL) for the metal oxide or varies across at least a majority of the article thickness (t) indicates stress generation within the article as a result of ion exchange. The variation in metal oxide concentration may be referred to herein as a metal oxide concentration gradient. Metal oxides with non-zero concentrations that vary from the first surface to the DOL or across a portion of the thickness may be described as generating stress within the glass-based article. The metal oxide concentration gradient or variation is created by chemical strengthening of the glass-based substrate, which exchanges a plurality of first metal ions in the glass-based substrate with a plurality of second metal ions.
[0025] As used herein, the terms "depth of exchange", "depth of layer" (DOL), "chemical depth of layer" and "depth of chemical layer" can be used interchangeably and generally describe the depth at which ion exchange facilitated by an ion exchange process (IOX) occurs for a particular ion. DOL refers to the depth within the glass-based article (i.e., the distance from the surface of the glass-based article to its interior region) at which a metal oxide or alkali metal oxide ion (e.g., a metal ion or an alkali metal ion) diffuses into the glass-based article and the concentration of the ion reaches a minimum as determined by glow discharge optical emission spectroscopy (GD-OES). In some embodiments, the DOL is indicated as the exchange depth of the slowest diffusing or largest ion introduced by the ion exchange (IOX) process. The DOL for potassium (DOL K ) is the depth at which the potassium content of the glass article reaches the potassium content of the underlying substrate. Na ) is the depth at which the sodium content of the glass article reaches the sodium content of the underlying substrate.
[0026] Unless otherwise specified, in this specification, CT and CS are expressed in megapascals (MPa), thickness is expressed in millimeters, and DOC and DOL are expressed in micrometers (μm).
[0027] Compressive stress (surface / peak CS, CS max ) and DOL sp is measured by a surface stress meter (FSM) using commercially available instruments such as the FSM-6000 manufactured by Orihara Seisakusho (Japan). Surface stress measurements rely on accurate measurement of the stress optical coefficient (SOC) associated with the birefringence of the glass. SOC is measured according to procedure C (glass disk method) described in ASTM standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the entire contents of which are incorporated herein by reference.
[0028] The maximum central tension (CT) or peak tension (PT) and stress retention values are measured using the scattered light polarimeter (SCALP) technique known in the art. The refractive near-field (RNF) technique or SCALP can be used to measure the stress profile and the depth of compression (DOC). When the RNF technique is used to measure the stress profile, the maximum CT value obtained by SCALP is used in the RNF technique. In particular, a force balance of the stress profile measured by RNF is obtained and calibrated against the maximum CT value obtained by the SCALP measurement. The RNF technique is described in U.S. Pat. No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample," which is incorporated herein by reference in its entirety. In particular, the RNF technique includes placing a glass article adjacent to a reference block, generating a polarization-switched light beam that is switched between orthogonal polarizations at a rate of 1 Hz to 50 Hz, measuring the amount of power in the polarization-switched light beam, and generating a polarization-switched reference signal, the measured amounts of power in each of the orthogonal polarizations being within 50% of each other. The method further includes transmitting the polarization-switched light beam through the glass sample and the reference block for different depths within the glass sample, and then relaying the transmitted polarization-switched light beam to a signal photodetector using relay optics, where the signal photodetector generates a polarization-switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining a profile characteristic of the glass sample from the normalized detector signal.
[0029] Summary of the properties of glass-based products The glass-based articles herein have a stress profile designed to have improved scratch resistance. The unique stress profile includes a desired potassium-sodium molar ratio at or near the surface of the glass-based article, and / or a desired compressive stress at the bending point, and / or a desired average compressive stress over a certain depth of the article.
[0030] In ion exchange, glasses having a base composition where the mole % of Na2O is lower than the mole % of Li2O can undergo significant ion exchange from potassium to lithium. Lithium can be easily ion-exchanged with sodium at a very fast diffusion rate based on their respective ionic radius sizes and can achieve a parabolic stress profile of lithium glass within a few hours. However, the ion exchange between lithium and potassium is much slower because the ionic radius of potassium is significantly larger than that of Na. The scratching performance of lithium-based glass compositions with mole % of Na2O << mole % of Li2O can be improved by using a high sodium salt (e.g., NaNO3) concentration in ion exchange to reduce the amount of ion exchange from potassium to lithium. When subjected to a treatment bath containing 100% NaNO3 salt, the scratching performance is significantly improved compared to a treatment bath containing 10% or less of the NaNO3 salt. Also, by using LiNO3 in combination with 10% or more of the NaNO3 salt in the treatment bath, the scratching performance is improved while being outside the range of brittleness. The load at which transverse cracks occur increases with the increase in sodium concentration in the treatment bath. This is also related to the surface of the glass where the mole % concentration ratio of potassium to sodium is similar (or even where the surface sodium concentration is higher).
[0031] The method described herein is advantageous in that by using specific bath conditions (high sodium concentration), the resulting stress profile leads to a glass having improved scratching performance and good drop performance. In this process, in contrast to the compositional changes seen with boron addition, the stress profile can achieve an improvement in scratch resistance. Ultimately, the user can improve or degrade the scratching performance of the glass by the ion exchange profile.
[0032] Now, we will refer in detail to lithium aluminosilicate glasses and scratch resistance according to various embodiments. Alkali aluminosilicate glasses have good ion exchangeability, and high strength and high toughness properties in alkali aluminosilicate glasses have been achieved using chemical strengthening processes. Sodium aluminosilicate glasses are high ion exchangeable glasses with high glass formability and quality. Lithium aluminosilicate glasses are high ion exchangeable glasses with high glass quality. Substituting Al2O3 into the silicate glass network enhances the interdiffusivity of monovalent cations in ion exchange. Glasses with high strength, high toughness and high indentation crack resistance can be achieved by chemical strengthening in a molten salt bath (e.g., KNO3 or NaNO3). The stress profile achieved by chemical strengthening can have various shapes that enhance the drop performance, strength, toughness and other attributes of the glass article, as well as the improvement of scratch resistance.
[0033] Therefore, lithium aluminosilicate glass, which has good physical properties, chemical durability and ion exchangeability, has attracted attention for use as protective glass. By different ion exchange processes, it can achieve larger central tension (CT), compression depth (DOC) and high compressive stress (CS). The stress profile described herein leads to improved fracture resistance of lithium-containing glass articles.
[0034] In the glass composition embodiments described herein, concentrations of components (e.g., SiO, AlO, LiO, NaO, etc.) are given in mole percent (mol%) on an oxide basis unless otherwise specified. It should be understood that any of the variously recited ranges for a component may be individually combined with any of the variously recited ranges for any other component.
[0035] Disclosed herein is an ion exchange method and stress profile for lithium aluminosilicate glass compositions. The stress profile is indicative of scratch resistance. Referring to FIG. 1, a glass has a thickness t and has a first region under compressive stress (e.g., first and second compressive stress layers 120, 122 in FIG. 1) extending from the surface of the glass to a depth of compression (DOC), and a second region under tensile stress or central tension (CT) (e.g., central region 130 in FIG. 1) extending from the DOC to a center or interior region of the glass.
[0036] The compressive stress (CS) typically has a maximum or peak value that occurs at the surface of the glass (but this does not have to be the case as the peak may occur at some depth from the surface of the glass) and CS varies with distance d from the surface as a function. Referring again to Figure 1, the first compressive layer 120 extends to a depth d1 from the first surface 110 and the second compressive layer 122 extends to a depth d2 from the second surface 112. Together these segments define the compression or CS of the glass 100.
[0037] The compressive stresses on both major faces (110, 112 in FIG. 1) are balanced by tension stored in the central region (130) of the glass.
[0038] The glass-based article has an alkali metal oxide with a non-zero concentration that varies from one or both of the first and second surfaces to a depth of layer (DOL) for the metal oxide. The non-zero concentration of the metal oxide that varies from the first surface creates a stress profile. The non-zero concentration may vary along a portion of the article thickness. In some embodiments, the concentration of the alkali metal oxide is non-zero and both vary along a thickness range of about 0·t to about 0.3·t. In some embodiments, the concentration of the alkali metal oxide is non-zero and varies along a thickness range of about 0·t to about 0.35·t, about 0·t to about 0.4·t, about 0·t to about 0.45·t, about 0·t to about 0.48·t, or about 0·t to about 0.50·t. The concentration variation may be continuous along the thickness range. The concentration variation may include a change in metal oxide concentration of about 0.2 mole % or more along a thickness segment of about 100 μm. The change in metal oxide concentration may be about 0.3 mol % or more, about 0.4 mol % or more, or about 0.5 mol % or more along a segment about 100 μm thick, which can be measured by methods known in the art, including microprobes.
[0039] In some embodiments, the variation in concentration may be continuous along a thickness segment ranging from about 10 μm to about 30 μm, In some embodiments, the concentration of alkali metal oxide decreases from the first surface to a value between the first surface and the second surface, and then increases from that value to the second surface.
[0040] The alkali metal oxide concentration may include two or more metal oxides (e.g., a combination of Na2O and KO). In some embodiments, when two metal oxides are used and the ions have different radii, the concentration of the ions with the larger radius is higher than the concentration of the ions with the smaller radius at shallower portions and the concentration of the ions with the smaller radius is higher than the concentration of the ions with the larger radius at deeper portions.
[0041] In one or more embodiments, the concentration gradient of the alkali metal oxide spans most of the thickness t of the article. In some embodiments, the concentration of the metal oxide may be about 0.5 mol % or more (e.g., about 1 mol % or more) along the entire thickness of the first and / or second sections, being highest at the first and / or second surfaces 0·t and decreasing substantially consistently to a value between the first and second surfaces. At that value, the concentration of the metal oxide is lowest along the entire thickness t, but even at that point the concentration is not zero. In other words, the non-zero concentration of that particular metal oxide extends along most of or the entire thickness t (as described herein). The total concentration of the particular metal oxide in the glass-based article may range from about 1 mol % to about 20 mol %.
[0042] The concentration of alkali metal oxide can be determined from the baseline amount of metal oxide in the glass-based substrate that is ion-exchanged to form the glass-based article.
[0043] In one or more embodiments, the glass-based article has a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO), averaged from the surface to a depth of 0.4 μm, that is 0 or more and 1.8 or less, or 0.2 or more, 0.4 or more, 0.6 or more, 0.8 or more, 1 or more, 1.2 or more, 1.4 or more, 1.6 or more and / or 1.7 or less, 1.5 or less, 1.3 or less, 1.1 or less, 0.9 or less, and all values and subranges therebetween. These molar ratios of KO to NaO contribute, at least in part, to the improved scratch resistance of the glass-based articles described herein.
[0044] In one or more embodiments, the glass-based article has a depth of spike layer (DOL spike ) is 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more and / or 8 μm or less, 7.5 μm or less, 7 μm or less (including all values and subranges therebetween).
[0045] In one or more embodiments, the glass-based article has a potassium depth of layer (DOL K) is 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more and / or 8 μm or less, 7.5 μm or less, 7 μm or less (including all values and subranges therebetween).
[0046] In one or more embodiments, the glass-based article may have a non-zero concentration of sodium (DOL) ranging from the surface to the depth of the glass-based article. Na ) is 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more and / or 8 μm or less, 7.5 μm or less, 7 μm or less (including all values and subranges therebetween).
[0047] In one or more embodiments, the glass-based article has an average compressive stress (CS) over a depth of 15 μm to 40 μm. avg ) is 115 MPa or greater, 120 MPa or greater, 125 MPa or greater, 130 MPa or greater, 135 MPa or greater, 140 MPa or greater, 145 MPa or greater, 150 MPa or greater, 155 MPa or greater, 160 MPa or greater, 165 MPa or greater, 170 MPa or greater (including all values and subranges therebetween).
[0048] In one or more embodiments, the glass-based article has a compressive stress at the bending point (CS k ) is 115 MPa or greater, 120 MPa or greater, 125 MPa or greater, 130 MPa or greater, 135 MPa or greater, 140 MPa or greater, 145 MPa or greater, 150 MPa or greater, 155 MPa or greater, 160 MPa or greater, 165 MPa or greater, 170 MPa or greater (including all values and subranges therebetween).
[0049] In one or more embodiments, the glass-based article has a compressive stress at the bending point (CS k ) is 115 MPa or greater, 120 MPa or greater, 125 MPa or greater, 130 MPa or greater, 135 MPa or greater, 140 MPa or greater, 145 MPa or greater, 150 MPa or greater, 155 MPa or greater, 160 MPa or greater, 165 MPa or greater, 170 MPa or greater (including all values and subranges therebetween).
[0050] In one or more embodiments, the glass-based article has a depth of compression (DOC) of 0.19t or more, 0.20t or more, 0.21t or more, 0.22t or more, 0.23t or more, 0.24t or more, 0.25t or more, and / or 0.30t or less, 0.29t or less, 0.28t or less, 0.27t or less, 0.26t or less, 0.25t or less, 0.24t or less, 0.23t or less (including all values and subranges therebetween).
[0051] In one or more embodiments, the glass-based article has a depth of compression (DOC) of 150 μm or more, 155 μm or more, 160 μm or more, 165 μm or more, 170 μm or more, including all values and subranges therebetween.
[0052] In one or more embodiments, the glass-based article has t in the range of 0.5 mm to 0.8 mm, and all values and subranges therebetween, and / or t can be 0.8 mm or less, 0.75 mm or less, 0.73 mm or less, 0.70 mm or less, 0.65 mm or less, 0.6 mm or less, 0.55 mm or less, 0.4 mm or less, 0.3 mm or less, or 0.2 mm or less, and / or 0.1 mm or more, including all values and subranges therebetween.
[0053] In one or more embodiments, the glass-based article has a maximum compressive stress (CS max ) is 500 MPa or greater, 550 MPa or greater, 600 MPa or greater, 650 MPa or greater, 700 MPa or greater, 750 MPa or greater, 800 MPa or greater, 850 MPa or greater, 900 MPa or greater, 950 MPa or greater, 1000 MPa or greater, 1050 MPa or greater, 1100 MPa or greater, 1150 MPa or greater, or 1200 MPa or greater (including all values and subranges therebetween).
[0054] In one or more embodiments, the glass-based article has a Li2O / Na2O molar ratio of greater than or equal to 0.10 and less than or equal to 0.63, including all values and subranges therebetween.
[0055] The glass-based article may have one or a combination of the following characteristics in combination with a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO) of 0 or more and 1.8 or less, averaged over a distance from the surface to a depth of 0.4 μm: a lithium aluminosilicate composition; a variable, non-zero concentration of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) of 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more and / or 8 μm or less, 7.5 μm or less, 7 μm or less, including all values and subranges therebetween. spike ); Average compressive stress (CS) over a depth of 15 μm to 40 μm of 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, 160 MPa or more, 165 MPa or more, 170 MPa or more (including all values and subranges therebetween) avg );Compressive stress at the inflection point (CS ) of 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, 160 MPa or more, 165 MPa or more, 170 MPa or more (including all values and subranges therebetween) k); a depth of compression (DOC) that is 0.19t or more, 0.20t or more, 0.21t or more, 0.22t or more, 0.23t or more, 0.24t or more, 0.25t or more, and / or 0.30t or less, 0.29t or less, 0.28t or less, 0.27t or less, 0.26t or less, 0.25t or less, 0.24t or less, 0.23t or less (including all values and subranges therebetween), and / or 150μm or more, 155μm or more, 160μm or more, 165μm or more, 170μm or more (including all values and subranges therebetween); a t in the range of 0.5mm to 0.8mm and all values and subranges therebetween, and / or 0.8 a maximum compressive stress (CS ) of 500 MPa or more, 550 MPa or more, 600 MPa or more, 650 MPa or more, 700 MPa or more, 750 MPa or more, 800 MPa or more, 850 MPa or more, 900 MPa or more, 950 MPa or more, 1000 MPa or more, 1050 MPa or more, 1100 MPa or more, 1150 MPa or more, or 1200 MPa or more, including all values and subranges therebetween; max ); a Li2O / Na2O molar ratio of 0.10 to 0.63, inclusive, including all values and subranges therebetween, and at a center portion of the glass-based article, the base composition comprises 9.39-25 mol% alumina (Al2O3), 0.1-20 mol% sodium oxide (Na2O), up to 9.01 mol% boron oxide (B2O3), and at least one alkaline earth metal oxide, with 15 mol%≦(R2O+R'O-Al2O3-ZrO2)-B2O3≦2 mol%, where R is Na and optionally one or more of Li, K, Rb, and Cs, and R' is one or more of Mg, Ca, Sr, and Ba.
[0056] The glass-based article may have a Depth of Spike Layer (DOL) of 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more, and / or 8 μm or less, 7.5 μm or less, 7 μm or less, including all values and subranges therebetween. spike), may have one or a combination of the following features: a lithium aluminosilicate composition; a variable, non-zero concentration of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO) averaged over a distance from the surface to a depth of 0.4 μm of 0 to 1.8; an average compressive stress (CS) over a depth of 15 μm to 40 μm of 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, 160 MPa or more, 165 MPa or more, 170 MPa or more, including all values and subranges therebetween. avg );Compressive stress at the inflection point (CS ) of 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, 160 MPa or more, 165 MPa or more, 170 MPa or more (including all values and subranges therebetween) k); a depth of compression (DOC) that is 0.19t or more, 0.20t or more, 0.21t or more, 0.22t or more, 0.23t or more, 0.24t or more, 0.25t or more, and / or 0.30t or less, 0.29t or less, 0.28t or less, 0.27t or less, 0.26t or less, 0.25t or less, 0.24t or less, 0.23t or less (including all values and subranges therebetween), and / or 150μm or more, 155μm or more, 160μm or more, 165μm or more, 170μm or more (including all values and subranges therebetween); a t in the range of 0.5mm to 0.8mm and all values and subranges therebetween, and / or 0.8 a maximum compressive stress (CS ) of 500 MPa or more, 550 MPa or more, 600 MPa or more, 650 MPa or more, 700 MPa or more, 750 MPa or more, 800 MPa or more, 850 MPa or more, 900 MPa or more, 950 MPa or more, 1000 MPa or more, 1050 MPa or more, 1100 MPa or more, 1150 MPa or more, or 1200 MPa or more, including all values and subranges therebetween; max ); a Li2O / Na2O molar ratio of 0.10 to 0.63, inclusive, including all values and subranges therebetween, and at a center portion of the glass-based article, the base composition comprises 9.39-25 mol% alumina (Al2O3), 0.1-20 mol% sodium oxide (Na2O), up to 9.01 mol% boron oxide (B2O3), and at least one alkaline earth metal oxide, with 15 mol%≦(R2O+R'O-Al2O3-ZrO2)-B2O3≦2 mol%, where R is Na and optionally one or more of Li, K, Rb, and Cs, and R' is one or more of Mg, Ca, Sr, and Ba.
[0057] The glass-based article may have an average compressive stress (CS) over a depth of 15 μm to 40 μm of 115 MPa or greater, 120 MPa or greater, 125 MPa or greater, 130 MPa or greater, 135 MPa or greater, 140 MPa or greater, 145 MPa or greater, 150 MPa or greater, 155 MPa or greater, 160 MPa or greater, 165 MPa or greater, 170 MPa or greater, including all values and subranges therebetween. avg ), may have one or a combination of the following features: a lithium aluminosilicate composition; a variable, non-zero concentration of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO), averaged over a distance from the surface to a depth of 0.4 μm, of 0 to 1.8; a spike layer depth (DOL) of 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more, and / or 8 μm or less, 7.5 μm or less, 7 μm or less, including all values and subranges therebetween. spike );Compressive stress at the inflection point (CS ) of 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, 160 MPa or more, 165 MPa or more, 170 MPa or more (including all values and subranges therebetween) k); a depth of compression (DOC) that is 0.19t or more, 0.20t or more, 0.21t or more, 0.22t or more, 0.23t or more, 0.24t or more, 0.25t or more, and / or 0.30t or less, 0.29t or less, 0.28t or less, 0.27t or less, 0.26t or less, 0.25t or less, 0.24t or less, 0.23t or less (including all values and subranges therebetween), and / or 150μm or more, 155μm or more, 160μm or more, 165μm or more, 170μm or more (including all values and subranges therebetween); a t in the range of 0.5mm to 0.8mm and all values and subranges therebetween, and / or 0.8 a maximum compressive stress (CS ) of 500 MPa or more, 550 MPa or more, 600 MPa or more, 650 MPa or more, 700 MPa or more, 750 MPa or more, 800 MPa or more, 850 MPa or more, 900 MPa or more, 950 MPa or more, 1000 MPa or more, 1050 MPa or more, 1100 MPa or more, 1150 MPa or more, or 1200 MPa or more, including all values and subranges therebetween; max ); a Li2O / Na2O molar ratio of 0.10 to 0.63, inclusive, including all values and subranges therebetween, and at a center portion of the glass-based article, the base composition comprises 9.39-25 mol% alumina (Al2O3), 0.1-20 mol% sodium oxide (Na2O), up to 9.01 mol% boron oxide (B2O3), and at least one alkaline earth metal oxide, with 15 mol%≦(R2O+R'O-Al2O3-ZrO2)-B2O3≦2 mol%, where R is Na and optionally one or more of Li, K, Rb, and Cs, and R' is one or more of Mg, Ca, Sr, and Ba.
[0058] In one embodiment, the glass-based article comprises a lithium aluminosilicate composition; varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) of 4 μm or greater and 8 μm or less; spike); and a molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm, the molar ratio being greater than or equal to 0 and less than or equal to 1.8.
[0059] In one embodiment, the glass-based article comprises a lithium aluminosilicate composition; varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) of 4 μm or greater and 8 μm or less; spike ); and the average compressive stress (CS ) from 15 μm to 40 μm deep of 115 MPa or more avg ).
[0060] In one embodiment, the glass-based article comprises a glass-based article having a non-zero concentration of sodium extending from the surface of the glass-based article to the depth of the glass-based article; an average compressive stress (CS ) of 150 MPa or greater extending from 15 μm to 40 μm in depth; avg ); and a molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm, the molar ratio being greater than or equal to 0 and less than or equal to 1.8.
[0061] Glass Substrate Examples of glasses that can be used as substrates include alkali-aluminosilicate glass compositions or alkali-containing aluminoborosilicate glass compositions, although other glass compositions are contemplated. Specific examples of glass-based substrates that can be used include, but are not limited to, alkali-aluminosilicate glasses, alkali-containing borosilicate glasses, alkali-aluminoborosilicate glasses, alkali-containing lithium aluminosilicate glasses, or alkali-containing phosphate glasses. Glass-based substrates have a base composition that can be characterized as ion-exchangeable. As used herein, "ion-exchangeable" means that a substrate having that composition is capable of exchanging cations located at or near the surface of the substrate with cations of the same valence that are larger or smaller in size.
[0062] In one or more embodiments, the glass-based substrate can include a lithium-containing aluminosilicate.
[0063] In embodiments, the glass-based substrate can be formed from any composition capable of forming a stress profile. In some embodiments, the glass-based substrate can be formed from a glass composition described in U.S. Patent Application Publication No. 16 / 202,691, entitled "Glasses with Low Excess Modifier Content," filed November 28, 2018, which is incorporated herein by reference in its entirety. In some embodiments, the glass article can be formed from a glass composition described in U.S. Patent Application Publication No. 16 / 202,767, entitled "Ion-Exchangeable Mixed Alkali Aluminosilicate Glasses," filed November 28, 2018, which is incorporated herein by reference in its entirety.
[0064] A glass-based substrate can be characterized by the manner in which it can be formed. For example, a glass-based substrate can be characterized as float formable (i.e., formed by a float process), downdrawable, particularly fusion formable or slot drawable (i.e., formed by a downdraw process such as a fusion draw process or a slot draw process). In an embodiment, the glass-based substrate can be roll formed.
[0065] Some embodiments of the glass-based substrates described herein can be formed by a down-draw process. The down-draw process produces glass-based substrates with uniform thickness and relatively untreated surfaces. Untreated surfaces that have minimal contact have higher initial strength because the average bending strength of a glass article depends on the amount and size of surface scratches. In addition, down-draw glass articles have very flat and smooth surfaces and can be used in their end use without expensive grinding and polishing.
[0066] Some embodiments of glass-based substrates may be described as fusion formable (i.e., formable using the fusion draw process). The fusion process employs a draw tank having a channel that receives molten glass frit. The channel has open-topped weirs on either side of the channel along the length of the channel. When the channel is filled with molten material, the molten glass overflows the weirs. Gravity causes the molten glass to flow down the outer surfaces of the draw tank as two flowing glass films that extend downwardly and inwardly and meet at a lower end of the draw tank. The two flowing glass films meet and fuse at this end to form a single flowing glass article. The fusion draw process offers the advantage that, as the two glass films flowing over the channels fuse together, neither of the outer surfaces of the resulting glass article comes into contact with any part of the apparatus. Thus, the surface properties of the fusion drawn glass article are not affected by such contact.
[0067] Some embodiments of the glass-based substrates described herein may be formed by a slot-draw process. The slot-draw process is different from the fusion-draw process. In the slot-draw process, molten raw glass is fed into a draw tank. At the bottom of the draw tank is an open slot with a nozzle that extends the length of the slot. The molten glass flows through the slot / nozzle and is drawn downward into an annealing area as a continuous glass article.
[0068] In one embodiment, the base composition comprises 9.39-25 mol% alumina (Al2O3), 0.1-20 mol% sodium oxide (Na2O), up to 9.01 mol% boron oxide (BO3), and at least one alkaline earth metal oxide, with 15 mol%≦(RO+RO-Al2O3-ZrO2)-BO3≦2 mol%, where R is Na and optionally one or more of Li, K, Rb, and Cs, and R′ is one or more of Mg, Ca, Sr, and Ba.
[0069] In one or more embodiments, the glass-based substrates described herein may exhibit an amorphous microstructure and may be substantially free of crystals or crystallites. In other words, in some embodiments, glass-based substrate articles exclude glass-ceramic materials.
[0070] Ion exchange (IOX) treatment Chemical strengthening of glass substrates having a basic composition is carried out by exchanging ion-exchanged glass substrates with cations (e.g., K + , Na + , Ag + This is done by placing the glass in a molten bath containing cations that diffuse into the glass while the smaller alkali ions (e.g. Na + , Li + ) diffuse into the molten bath. The replacement of smaller cations with larger cations creates compressive stresses near the top surface of the glass. To balance the compressive stress near the surface, tensile stresses develop within the glass.
[0071] With respect to the ion exchange process, it can independently be a thermal diffusion process or an electrodiffusion process. Non-limiting examples of ion exchange processes in which glass is immersed in multiple ion exchange baths with washing and / or annealing steps between immersions include U.S. Patent No. 8,561,429, issued October 22, 2013, which claims priority from U.S. Provisional Patent Application No. 61 / 079,995, filed July 11, 2008, entitled "Glass with Compressive Surface for Consumer Applications," which strengthens glass by immersion in salt baths of different concentrations in multiple successive ion exchange treatments, and U.S. Patent No. 8,561,429, issued October 22, 2013, by Douglas C. Allan et al., which claims priority from U.S. Provisional Patent Application No. 61 / 084,398, filed July 29, 2008, entitled "Dual Stage Ion Exchange for Chemical Strengthening of Glass," which strengthens glass by ion exchange in a first bath diluted with effluent ions, followed by immersion in a second bath having a lower concentration of effluent ions than the first bath. No. 8,312,739 to M. Lee et al., the entire contents of which are incorporated herein by reference.
[0072] It should be understood that after the ion exchange process, the composition of the surface of the glass article may differ from the composition of the as-formed glass article (i.e., the glass article before it was subjected to the ion exchange process). This is due to the presence of certain alkali metal ions, such as Li, in the as-formed glass. + or Na + However, larger alkali metal ions, such as Na + or K + However, the glass composition at or near the center of the depth of the glass article, in embodiments, still has the composition of the as-formed glass article.
[0073] In one aspect, a method of making a glass-based article includes subjecting a glass-based substrate having opposed first and second surfaces defining a substrate thickness (t), the substrate having a lithium aluminosilicate composition, to an ion exchange treatment comprising a molten salt bath having a sodium salt concentration ranging from 8 mol % to 100 mol %, and varying non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; a spike layer depth (DOL) ranging from 4 μm to 8 μm from the surface. spike ) a compressed layer extending from the surface to a depth of 0.4 μm; and forming a glass-based article having a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO) between 0 and 1.8, averaged over a distance from the surface to a depth of 0.4 μm.
[0074] Glass-based articles made by the methods herein may include one or more of the following: an average compressive stress (CS) over a depth of 15 μm to 40 μm of 115 MPa or greater; avg ); and a depth of compression (DOC) of 0.19t or more and / or 150 μm or more. The base composition of the glass-based substrate is a molar ratio of sodium oxide (Na2O) to lithium oxide (Li2O) of 0.63 or less. The sodium salts may include NaNO3, Na2CO3, Na3PO4, Na2SO4, Na3BO3, NaCl, or combinations thereof.
[0075] In one embodiment, the method is carried out using a single ion exchange process, and the molten salt bath includes a sodium salt in an amount of 8% to 100% by weight, a lithium salt in an amount of 0% to 10% by weight, and a potassium salt in an amount of 0% to 90% by weight. The sodium salt may include sodium nitrate (NaNO3), the lithium salt includes lithium nitrate (LiNO3), and the potassium salt includes potassium nitrate (KNO3).
[0076] In one embodiment, the method is carried out using a double ion exchange process, where a first molten salt bath includes a sodium salt in an amount of 8% to 100% by weight, a lithium salt in an amount of 0% to 10% by weight, and a potassium salt in an amount of 0% to 90% by weight, and a second molten salt bath includes a sodium salt in an amount of 8% to 100% by weight, a lithium salt in an amount of 0% to 10% by weight, and a potassium salt in an amount of 0% to 90% by weight. In each molten salt bath, the sodium salt may include sodium nitrate (NaNO3), the lithium salt includes lithium nitrate (LiNO3), and the potassium salt includes potassium nitrate (KNO3).
[0077] The methods herein can be effective in forming a glass-based substrate having a potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio of 0 to 1.8 averaged over a distance from the surface to a depth of 0.4 μm.
[0078] The method herein uses the depth of spike layer (DOL spike ) can be effective for forming a glass-based substrate having a grain size of 4 μm or more and 8 μm or less.
[0079] final product The glass-based articles disclosed herein can be incorporated into another article, such as an article having a display (or display device) (e.g., consumer electronics including mobile phones, tablets, computers, navigation systems, etc.), building products, transportation (e.g., automobiles, trains, aircraft, ships, etc.), appliances, or any article that requires some transparency, scratch resistance, abrasion resistance, or combinations thereof. Exemplary articles incorporating any of the glass articles disclosed herein are shown in Figures 3A and 3B. Specifically, Figures 3A and 3B show a consumer electronic device 300 comprising a housing 302 having a front surface 304, a rear surface 306, and a side surface 308, electrical components (not shown) at least partially or completely within the housing and including at least a controller, memory, and a display 310 at or adjacent to the front surface of the housing, and a cover 312 at or over the front surface of the housing to cover the display. In some embodiments, the cover 312 and / or the housing 302 can include any of the glass articles disclosed herein. EXAMPLES
[0080] The various embodiments will be further clarified by the following examples, in which the examples before being tempered are referred to as "substrates." After being subjected to tempering, the examples are referred to as "articles" or "glass-based articles."
[0081] Glass substrates according to compositions A to C were ion exchanged and the resulting articles were tested.
[0082] Compositions A and B had the following compositions: Composition A: 17.83 mol% Al2O3, 6.11 mol% B2O3, 4.41 mol% MgO, 1.73 mol% Na2O, 58.39 mol% SiO2, 0.08 mol% SnO2, 0.18 mol% K2O, 0.02 mol% Fe2O3, 0.58 mol% CaO and 10.66 mol% Li2O (0.00 mol% SrO, 0.00 mol% ZnO and 0.00 mol% P2O5); and a Na2O / Li2O molar ratio of 0.16. Composition B: 12.88 mol% Al2O3, 1.84 mol% B2O3, 2.86 mol% MgO, 2.39 mol% Na2O, 70.96 mol% SiO2, 0.07 mol% SnO2, 0.02 mol% Fe2O3, 8.13 mol% Li2O and 0.85 mol% ZnO (0.00 mol% K2O, 0.00 mol% CaO, 0.00 mol% SrO and 0.00 mol% P2O5); and a Na2O / Li2O molar ratio of 0.29.
[0083] Composition C had the following composition: Composition C: 15.17 mol% Al2O3, 6.73 mol% B2O3, 1.02 mol% MgO, 4.32 mol% Na2O, 63.27 mol% SiO2, 0.03 mol% SnO2, 0.02 mol% Fe2O3, 1.55 mol% CaO, 6.86 mol% Li2O, and 1.03 mol% SrO (0.00 mol% K2O and 0.00 mol% P2O5, 0.00 mol% ZnO); and a Na2O / Li2O molar ratio of 0.63.
[0084] Several glass articles were made under various ion exchange conditions containing 0 mole % sodium salt to 100 mole % sodium salt. Scratch testing of the example glass articles was completed using a Bruker universal mechanical tester (UMT) equipped with a Gilmore Diamonds Knoop-shaped diamond tip. The tip was loaded against the surface of the glass article at a rate of 0.14 N / s to the desired load of 5 N or 8 N, and the tip was pulled across the article at a rate of 9.34 mm / min to create 2 to 5 scratches per load. The diamond tip was then unloaded at a rate of 0.14 N / s.
[0085] Examples 1 to 6 and Examples A to D (Comparative) - Glass articles based on composition A - SIOX Glass articles were formed based on substrates according to composition A that were ion-exchanged according to the bath conditions listed in Table 1A.
[0086] [Table 1A]
[0087] Scratch data is shown in Table 1B.
[0088] [Table 1B]
[0089] Example A (comparative) in Table 1B shows that when no sodium was present in the ion exchange bath, a transverse crack occurred in the glass article at 5N. When the load was increased to 8N, the article broke. As the sodium concentration in the ion exchange bath increased, the threshold for transverse crack formation increased. Example B (comparative) with a bath of 6%Na / 94%K showed transverse cracks at 5N, and the article did not break when loaded to 8N. Example 1 with a condition of 12%Na further increased the threshold, with no transverse cracks observed at 5N, but some transverse cracks at 8N, which were fewer than those of Example B. For Example 6, where the bath concentration was increased to 30%Na, no transverse cracks were observed at 5N, but some transverse cracks occurred at 8N. For Example 2, where the bath concentration was increased to 100%Na, no transverse cracks were observed at 5N or 8N. However, the articles of Examples 2 and 6 were fragile. At a nominal 10% NaNO3 concentration, similar behavior is observed for thicknesses between 0.75 mm (Example 4) and 0.8 mm (Example 3).
[0090] 4-8 present GDOES elemental profiles of oxide molar concentration as a function of depth in the glass article from the first surface (0 μm) for Examples 1, C, D, 4 and 6, respectively.
[0091] For Example 1 in FIG. 4, the average under the curve concentration values measured over a distance from 0 μm to 0.4 μm were 4.1 for Na2O mole % and 4.82 for K2O mole %. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 1.16. The potassium layer depth (DOL K ) was 4.7 μm.
[0092] For Example C (comparative) in FIG. 5, the average under the curve concentration values measured over a distance from 0 μm to 0.4 μm were 4.2 for Na2O mole % and 8.4 for K2O mole %. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 2.0. The potassium layer depth (DOL K ) was 7.2 μm.
[0093] For Example D (comparative) in FIG. 6, the average under the curve concentration values measured over a distance from 0 μm to 0.4 μm were 3.7 for Na2O mole % and 8.1 for K2O mole %. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 2.21. The potassium layer depth (DOL K ) was 7.9 μm.
[0094] For Example 4 in FIG. 7, taking the average under the curve of the concentration values measured over a distance from 0 μm to 0.4 μm, the average Na2O mole % was 4.64 and the average K2O mole % was 4.88. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 1.05. The potassium layer depth (DOL K ) was 5.0 μm.
[0095] For Example 6 in FIG. 8, taking the average under the curve of the concentration values measured over a distance from 0 μm to 0.4 μm, the average Na2O mole % was 8.78 and the average K2O mole % was 3.31. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 0.38. The potassium layer depth (DOL K ) was 6.2 μm.
[0096] The scratch resistance of Example 1, with an average molar ratio of K2O to Na2O of 1.25 over the distance from 0 μm to 0.4 μm, was better than that of Examples C and D, with ratios of 2.0 and 2.27, respectively. Both Examples 4 and 6, with ratios of 1.05 and 0.38, respectively, showed excellent scratch resistance.
[0097] From this it can be concluded that, in general, a stress profile favorable for scratch resistance is one in which the mole % Na2O at or near the surface is comparable to, or within a few mole % of, the mole % K2O. Furthermore, the preferred average molar ratio of K2O to Na2O over the distance from 0 μm to 0.4 μm is greater than or equal to 0 and less than or equal to 1.8, including all values and ranges therebetween.
[0098] 9 is a graph of stress (MPa) versus position (μm) from the surface for Examples 1, 3, and B, all of the same thickness. Although the two inventive articles and one comparative article show similar compressive stresses at depths of 10-30 μm, Example 1, with its higher Na mole % in the salt bath, exhibited a significantly increased load at which transverse cracks occurred compared to Example B, as reported in Table 1B.
[0099] For Examples 1 and 3, both of which are shown in FIG. 9, the average compressive stress over a depth of 15 μm to 40 μm, based on the average area under the curve in FIG. 9, was both 140 MPa. Example 1 had a depth of layer (DOL) of 5.1 μm. spike ) and CS of 138 MPa knee Example 3 had a depth of layer (DOL) of 5.3 μm. spike ) and CS of 141 MPa knee had the following characteristics:
[0100] 10 is a graph of stress (MPa) versus position from surface (μm) for Examples 4 and 5. Example 4, using 10% NaNO3 / 1.2% LiNO3, produced a stress profile with a surface CS about 40 MPa higher, which may be beneficial for overstress failure.
[0101] Examples 7 and 8, and Example E (Comparative) - Glass Article Based on Composition B - SIOX Glass articles were formed based on substrates according to composition B that were ion-exchanged according to the bath conditions listed in Table 2A.
[0102] [Table 2A]
[0103] Scratch data is shown in Table 2B.
[0104] [Table 2B]
[0105] Example E (comparative) in Table 2B shows that when less sodium was present in the ion exchange bath, transverse cracks occurred in the glass article at both 5N and 8N. As the sodium concentration of the ion exchange bath increased, the threshold for transverse crack formation increased. Example 7, with a condition of 12% Na, further increased the threshold, with no transverse cracks observed at 5N, but transverse cracks seen at 8N. Example 8, where the bath concentration was increased to 100% Na, did not observe transverse cracks at 5N or 8N.
[0106] For Example 7 in FIG. 11, taking an average under the curve of the concentration values measured over a distance from 0 μm to 0.4 μm, the average Na2O mole % was 3.55 and the average K2O mole % was 4.47. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 1.26. The potassium layer depth (DOL K ) was 6.1 μm.
[0107] 12 is a graph of stress (MPa) versus position from the surface (μm) for Examples 7 and E. CS of Example 7 knee (116MPa) is the CS of Comparative Example E knee This is an improvement of approximately 16 MPa compared to approximately 100 MPa.
[0108] For Example 7 shown in FIG. 12, the average compressive stress over a depth of 15 μm to 40 μm, based on the average area under the curve in FIG. 12, was 102 MPa. Example 7 had a depth of layer (DOL) of 6.5 μm. spike ) and CS of 116 MPa knee had the following characteristics:
[0109] Example F (Comparative) - Glass article based on composition C - DIOX Glass articles were formed based on substrates according to composition C that were ion-exchanged according to the bath conditions listed in Table 3A.
[0110] [Table 3A]
[0111] Scratch data is shown in Table 3B.
[0112] [Table 3B]
[0113] Figure 13 presents the GDOES elemental profile of oxide molar concentration as a function of depth in the glass article from the first surface (0 μm) for Example F (comparative). Taking an average under the curve of concentration values measured over a distance of 0 μm to 0.4 μm, the average Na2O mole % was 3.15 and the average K2O mole % was 7.5. The resulting potassium dioxide (K2O) to sodium dioxide (Na2O) molar ratio was 2.37.
[0114] 14 is a graph of stress (MPa) versus position (μm) from the surface for Examples E and F. At the center of the glass, Example E (comparative) had a Na2O / Li2O molar ratio of 0.29, while Example F (comparative) had a Na2O / Li2O molar ratio of 0.63. The two glass compositions had comparable stress profiles.
[0115] Example F (comparative) in Table 3B shows that no transverse cracks were observed upon DIOX treatment at both 5N and 8N. Example E (comparative) in Table 2B shows that transverse cracks occurred in the glass article at both 5N and 8N when less sodium was present in the ion exchange bath. The scratch performance was improved (no transverse cracks were observed at 8N) for a similar stress profile (FIG. 14) when the glass composition had a Na2O / Li2O molar ratio of 0.63 (Example F) versus 0.29 (Example E) in the center of the glass. At a Na2O / Li2O molar ratio of 0.63, the K in the salt + The IOX value of Li in the glass is low, and K + exchanges with Na in the glass, and Na in the salt +The large K ions are exchanged with the Li ions in the glass. Therefore, the molar volume of the glass in the surface layer did not decrease significantly even when the large K ions were exchanged with the small Na ions to embrittle the surface.
[0116] For Example F (comparative) shown in FIG. 14, the average compressive stress over a depth of 15 μm to 40 μm, based on the average area under the curve in FIG. 14, was 92 MPa. Example F had a depth of layer (DOL) of 8.1 μm. spike ) and CS of 109 MPa knee had the following characteristics:
[0117] Examples 9 and 10 - Glass articles based on composition A - DIOX Glass articles were formed based on substrates according to composition A that were ion-exchanged according to the bath conditions listed in Table 4A.
[0118] [Table 4A]
[0119] Scratch data is shown in Table 4B.
[0120] [Table 4B]
[0121] As shown in Examples 9 and 10 of Table 4B, scratch performance using high Na (15%) DIOX to achieve high surface CS (FIG. 15) maintained scratch performance without transverse cracks at 5N. Both DIOX conditions have a first step with high Na salt (e.g., greater than 10% NaNO3) with sufficient %Li to achieve deep compression depth and still control fragility, and a second step with high Na salt without Li for a short time to build a high CS spike on the surface. Using this DIOX approach, it is possible to achieve CS of about 700-800 MPa without transverse cracks in Li-containing glass compositions with Na2O / Li2O molar ratios less than 0.63.
[0122] Figure 15 is a graph of stress (MPa) versus position (μm) from the surface for Examples 1, 9 and 10, and B (comparative). Examples 9 and 10 using DIOX produced stress profiles with high surface compressive stress (CS) along with good scratch performance, as measured by the absence of cross cracks at 5N (Table 4B). The DIOX stress profiles of Examples 9 and 10 also have higher inflection point stresses compared to the SIOX stress profiles of Example B (comparative) (6% Na, surface CS of 725 MPa), which had cross cracks at 5N, and Example 1 (12% Na, 2% Li, surface CS of 603 MPa), which did not have cross cracks at 5N.
[0123] For Examples 9 and 10, both of which are shown in FIG. 15, the average compressive stress over a depth of 15 μm to 40 μm, based on the average area under the curve in FIG. 15, was 203 MPa and 174 MPa, respectively. Example 9 had a depth of layer (DOL) of 4.4 μm. spike ) and CS of 280 MPa knee Example 10 had a depth of layer (DOL) of 5.2 μm. spike ) and CS of 233 MPa knee had the following characteristics:
[0124] Examples G-I (Comparative) - Glass Article Based on Composition A - DIOX Glass articles were formed based on substrates according to composition A that were ion-exchanged according to the bath conditions listed in Table 5A.
[0125] [Table 5A]
[0126] Scratch data is shown in Table 5B.
[0127] [Table 5B]
[0128] As shown in Table 5B, for Example G (comparative), which uses high Na (15%) in the first DIOX step followed by a long (>30 min) second step with low Na salt (<10% NaNO3) without Li, glasses with Na2O / Li2O molar ratios less than 0.63 showed transverse cracks at 5 N. Similarly, for Example H (comparative), which uses low Na (5%) in the first DIOX step followed by a second step with high Na salt (15% NaNO3) without Li, glasses with Na2O / Li2O molar ratios less than 0.63 also showed transverse cracks at 5 N.
[0129] FIG. 16 is a graph of stress (MPa) versus position (μm) from the surface for Examples 1 and 10, and B and G (comparative). Example G (comparative) and Example 10 were DIOX treated, resulting in stress profiles with high surface CS. Example G (comparative) had poor scratch performance, and Example 10 had good scratch performance as measured by the absence of transverse cracks at 5N. The stress profile for Example G (comparative) had a surface CS of 828 MPa, and Example 10 had a surface CS of 726 MPa. In FIG. 16, the stress profiles are compared to the SIOX stress profiles for Example B (comparative) (6% Na, surface CS is 725 MPa), which had transverse cracks at 5N, and Example 1 (12% Na, 2% Li, surface CS is 603 MPa), which did not have transverse cracks at 5N.
[0130] All compositional components, relationships and ratios described herein are presented in mole percent unless otherwise specified. All ranges disclosed herein include all ranges and subranges encompassed within the broadly disclosed range, whether set forth before or after the range is disclosed.
[0131] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, it is intended that the specification cover modifications and variations of the various embodiments described herein, provided that such modifications and variations come within the scope of the appended claims and their equivalents.
[0132] Preferred embodiments of the present invention will be described below in detail.
[0133] EMBODIMENT 1 Lithium aluminosilicate compositions; Varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; Spike layer depth (DOL) between 4μm and 8μm spike ); and A molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm in the glass-based article, between 0 and 1.8 Glass-based articles including:
[0134] EMBODIMENT 2 The glass-based article has an average compressive stress (CS avg 2. The glass-based article of embodiment 1, having a thickness of 100 nm to 150 nm.
[0135] EMBODIMENT 3 Compressive stress at bending point above 115MPa (CS knee ), and spike 3. The glass-based article of embodiment 1 or 2, wherein the grain size is 4.4 μm or more.
[0136] EMBODIMENT 4 Lithium aluminosilicate compositions; Varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; Spike layer depth (DOL) between 4μm and 8μm spike ); and The average compressive stress (CS ) across the depth of the glass-based article from 15 μm to 40 μm is 115 MPa or more. avg ) Glass-based articles including:
[0137] EMBODIMENT 5 5. The glass-based article of embodiment 4, comprising a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO), averaged over a distance from the surface to a depth of 0.4 μm in the glass-based article, of 0 to 1.8.
[0138] EMBODIMENT 6 Compressive stress at bending point (CS knee 6. The glass-based article of any one of claims 1 to 5, wherein the compressive strength (MPa) is 120 MPa or more.
[0139] EMBODIMENT 7 Said CS knee 7. The glass-based article of embodiment 6, wherein the compressive strength is 125 MPa or more.
[0140] EMBODIMENT 8 Said CS knee 7. The glass-based article of embodiment 6, wherein the compressive strength is 130 MPa or more.
[0141] EMBODIMENT 9 Varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; The average compressive stress (CS ) across the depth of the glass-based article from 15 μm to 40 μm is 150 MPa or more. avg ); and A molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm in the glass-based article, between 0 and 1.8 Glass-based articles including:
[0142] EMBODIMENT 10 10. The glass-based article of embodiment 9, comprising a lithium aluminosilicate composition.
[0143] EMBODIMENT 11 thickness t; Varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; Depth of compaction (DOC) of 0.19t or more; Spike layer depth (DOL) between 4μm and 8μm spike ); and A molar ratio of potassium dioxide (K2O) to sodium dioxide (Na2O) averaged over a distance from the surface to a depth of 0.4 μm in the glass-based article, between 0 and 1.8 Glass-based articles including:
[0144] EMBODIMENT 12 12. The glass-based article of any one of claims 1 to 11, wherein the compression depth is 150 μm or more.
[0145] EMBODIMENT 13 13. The glass-based article of embodiment 12, wherein the compression depth is 155 μm or more.
[0146] EMBODIMENT 14 13. The glass-based article of embodiment 12, wherein the compression depth is 160 μm or more.
[0147] EMBODIMENT 15 15. The glass-based article of any one of claims 1 to 14, wherein the molar ratio of sodium oxide (Na2O) to lithium oxide (Li2O) at the center of the glass-based article is 0.63 or less.
[0148] EMBODIMENT 16 16. The glass-based article of any one of claims 1 to 15, wherein the glass-based article has a base composition of 9.39-25 mol% alumina (Al2O3), 0.1-20 mol% sodium oxide (Na2O), up to 9.01 mol% boron oxide (BO3), and at least one alkaline earth metal oxide, in a central portion thereof, where 15 mol%≦(RO+RO-Al2O3-ZrO2)-BO3≦2 mol%, where R is Na and optionally one or more of Li, K, Rb, and Cs, and R′ is one or more of Mg, Ca, Sr, and Ba.
[0149] EMBODIMENT 17 17. The glass-based article of any one of the previous embodiments, comprising a Knoop scratch initiation threshold of 5 N or greater.
[0150] EMBODIMENT 18 18. The glass-based article of claim 17, wherein the Knoop scratch initiation threshold is 8 N or greater.
[0151] EMBODIMENT 19 The glass-based article has a maximum compressive stress (CS max 19. The glass-based article of any one of the preceding claims, having a.
[0152] EMBODIMENT 20 The DOL spike DOL K 20. The glass-based article of any one of the preceding claims, wherein the glass-based article is substantially the same as
[0153] EMBODIMENT 21 a housing having a front surface, a rear surface and a side surface; electrical components disposed at least partially within said housing, said electrical components including at least a controller, a memory, and a display, said display disposed at or adjacent to said front surface of said housing; a cover disposed on the display; 21. A consumer electronics product comprising: at least a portion of at least one of the housing and the cover comprising the glass-based article of any one of claims 1 to 20.
[0154] EMBODIMENT 22 1. A method of making a glass-based article, comprising: subjecting a glass-based substrate having opposed first and second surfaces defining a substrate thickness (t) and having a lithium aluminosilicate composition to an ion exchange process comprising a molten salt bath having a sodium salt concentration in the range of 8 mol % or more and 100 mol % or less to form a glass-based article. Including, The glass-based article is varying, non-zero concentrations of sodium extending from the surface of the glass-based article to the depth of the glass-based article; The depth of the spike layer (DOL) from the surface is 4 μm to 8 μm. spike ) compression layer; and 1. The method of claim 1, further comprising: a molar ratio of potassium dioxide (KO) to sodium dioxide (NaO) averaged over a distance from the surface to a depth of 0.4 μm into the glass-based article of between 0 and 1.8.
[0155] EMBODIMENT 23 The glass-based article has the following characteristics: The average compressive stress (CS) over a depth of 15 μm to 40 μm is 115 MPa or more. avg ); and Depth of compression (DOC) ≥ 0.19t and / or ≥ 150μm 23. The method of embodiment 22, comprising one or more of the following:
[0156] EMBODIMENT 24 24. The method of claim 22 or 23, wherein the base composition of the glass-based substrate comprises a molar ratio of sodium oxide (Na2O) to lithium oxide (Li2O) of 0.63 or less.
[0157] EMBODIMENT 25 25. The method of any one of embodiments 22 to 24, wherein the sodium salt comprises NaNO3, Na2CO3, Na3PO4, Na2SO4, Na3BO3, NaCl, or a combination thereof.
[0158] EMBODIMENT 26 26. The method of any one of embodiments 22 to 25, wherein the method is performed using a single ion exchange process, the molten salt bath comprising sodium salt in an amount of 8% to 100% by weight, lithium salt in an amount of 0% to 10% by weight, and potassium salt in an amount of 0% to 90% by weight.
[0159] EMBODIMENT 27 27. The method of embodiment 26, wherein the sodium salt comprises sodium nitrate (NaNO3), the lithium salt comprises lithium nitrate (LiNO3), and the potassium salt comprises potassium nitrate (KNO3).
[0160] EMBODIMENT 28 This is done using a double ion exchange process, the first molten salt bath comprises a sodium salt in an amount of 8% by mass or more and 100% by mass or less, a lithium salt in an amount of 0% by mass or more and 10% by mass or less, and a potassium salt in an amount of 0% by mass or more and 90% by mass or less; 26. The method of any one of embodiments 22 to 25, wherein the second molten salt bath comprises a sodium salt in an amount of from 8% to 100%, by weight, a lithium salt in an amount of from 0% to 10%, by weight, and a potassium salt in an amount of from 0% to 90%, by weight.
[0161] EMBODIMENT 29 29. The method of embodiment 28, wherein in each molten salt bath, the sodium salt comprises sodium nitrate (NaNO3), the lithium salt comprises lithium nitrate (LiNO3), and the potassium salt comprises potassium nitrate (KNO3).
Claims
1. Lithium aluminosilicate compositions; Varying non-zero concentrations of sodium ranging from 1 mol % to 20 mol % extending from the surface of the glass-based article to the depth of the glass-based article; Spike layer depth (DOL) of 4 μm to 8 μm spike ). Potassium oxide (K) averaged over a distance from the surface to a depth of 0.4 μm of the glass-based article is 0 or more and 1.8 or less. 2 O) and sodium oxide (Na 2 O); and a molar ratio of sodium oxide (Na 2 O) to lithium oxide (Li 2 O) at the center of the glass-based article of 0.63 or less; Glass-based articles, including
2. The glass-based article has an average compressive stress (CS) of 115 MPa or more across a depth of the glass-based article from 15 μm to 40 μm. avg 2. The glass-based article of claim 1, having a
3. Compressive stress at bending point (CS knee 3. The glass-based article according to claim 1 or 2, wherein the compressive strength is 120 MPa or more.
4. 4. The glass-based article according to any one of claims 1 to 3, wherein the compression depth is 150 μm or more.
5. The Knoop scratch initiation threshold is 5 N or more, and the potassium oxide (K 2 O) and sodium oxide (Na 2 The glass-based article according to any one of claims 1 to 4, wherein the molar ratio of 0 to 1.8 is 0.4 or more and 1.8 or less.
6. The glass-based article has a maximum compressive stress (CS max 6. The glass-based article of claim 1 , wherein the glass-based article has a thickness of 100 nm to 150 nm.
7. a housing having a front surface, a rear surface and a side surface; electrical components disposed at least partially within said housing, said electrical components including at least a controller, a memory, and a display, said display disposed at or adjacent to said front surface of said housing; a cover disposed on the display; 7. A consumer electronics product comprising: at least a portion of at least one of the housing and the cover comprising the glass-based article of any one of claims 1 to 6.
8. 1. A method of making a glass-based article, comprising: subjecting a glass-based substrate having opposed first and second surfaces defining a substrate thickness (t) and having a lithium aluminosilicate composition to an ion exchange process comprising a molten salt bath having a sodium salt concentration in the range of 10% to 100% by weight to form a glass-based article. and the glass-based article comprises: Varying non-zero concentrations of sodium ranging from 1 mol % to 20 mol % extending from the surface of the glass-based article to the depth of the glass-based article; The depth of the spike layer (DOL) from the surface is 4 μm or more and 8 μm or less. spike ) compression layer; 0 or more and 1.8 or less, averaged over a distance from the surface to a depth of 0.4 μm of the glass-based article (K 2 O) and sodium oxide (Na 2 O); and A molar ratio of sodium oxide (Na 2 O) to lithium oxide (Li 2 O) in the basic composition of the glass-based substrate of 0.63 or less. A method comprising:
Citation Information
Patent Citations
Glass compositions containing lithia-alumina-silica and glass suitable for chemical tempering and articles manufactured using chemically tempered glass
JP2007527354A
Methods for Characterizing Lithium-Containing Glasses Chemically Strengthened by Ion Exchange
JP2018527282A
Glass-based articles including a stress profile comprising two regions, and methods of making
US20170295657A1
Glass-based articles including a metal oxide concentration gradient
US20170305786A1
Lithium containing glass or glass ceramic article with modified k2o profile near the glass surface
WO2018143991A1